Imaging and detecting intercellular tensile forces in spheroids and embryoid bodies using lipid-modified DNA probes - Tian, Qian; Yang, Feiyu; Jiang, Han; Bhattacharyya, Priyanka; Xie, Tianfa; Ali, Ahsan Ausaf; Sun, Yubing; You, Mingxu (Frontiers in Cell and Developmental Biology, 2023)
Cells continuously experience and respond to physical forces. Our ability to measure these mechanical cues is essential for understanding various mechanosensing and mechanotransduction processes. While multiple strategies have been developed to study mechanical forces within two-dimensional (2D) cell culture monolayers, the force measurement at cell-cell junctions in three-dimensional (3D) cell models is still rare. Considering that cells are exposed to forces from 3D directions, measuring these molecular forces in their native environment is thus highly critical for the better understanding of different development and disease processes. We have recently developed a type of DNA-based molecular probe for measuring intercellular tensile forces in 2D cell models. Herein, we will report the further development and first-time usage of these molecular tension probes to visualize and detect mechanical forces within 3D spheroids and embryoid bodies (EBs). These probes can spontaneously anchor onto live cell membranes via the attached lipid moieties. By varying the concentrations of these DNA probes and their incubation time, we have first characterized the kinetics and efficiency of probe penetration and loading onto tumor spheroids and stem cell EBs of different sizes. After optimization, we have further imaged and measured E-cadherin-mediated forces in these 3D spheroids and EBs for the first time. Our results indicated that these DNA-based molecular tension probes can be used to study the spatiotemporal distributions of target mechanotransduction processes. These powerful imaging tools may be potentially applied to fill the gap between ongoing research of biomechanics in 2D systems and that in real 3D cell complexes.